Interference in a Language and Culture Communication - Gashimov, Elchin (Allure Journal, 2023)
International communication is one important aspect in a dialogue of culture and in a process of communication we should concentrate in a problem of the interrelated phenomena of language and culture within the context of bilingual communication. Language and culture interference are important aspect to be considered with regard to teaching of plurilingual learners, whose communicative competence is formed on the basis of several linguistic and cultural systems that interact with each other and exert mutual influence. Interference is an important aspect not only in linguistic, not only in the method of teaching but also in culture too. After pandemic era we practically have a new view of communication - Online communication, that is defined as perceptual-verbal interaction connected with acts of cognition and creation of meaning-forming systems, manifested in a whole set of principles, among which there are: 1) dialogueness and communicability; 2) visual-perceptual experience; 3) interpersonal communication; 4) a tool for cross-cultural dialogue; 5) a linguistic component.